Imaging Membrane Repair in Single Cells Using Correlative Light and Electron Microscopy. Issue 1 (7th August 2018) - Croissant, Coralie; Bouvet, Flora; Tan, Sisareuth; Bouter, Anthony
Abstract: Many cells possess the ability to repair plasma membrane disruption in physiological conditions. Growing evidence indicates a correlation between membrane repair and many human diseases. For example, a negative correlation is observed in muscle where failure to reseal sarcolemma may contribute to the development of muscular dystrophies. Instead, a positive correlation is observed in cancer cells where membrane repair may be exacerbated during metastasis. Here we describe a protocol that combines laser technology for membrane damage, immunostaining with gold nanoparticles and imaging by fluorescence microscopy and transmission electron microscopy (TEM), which allows the characterization of the molecular machinery involved in membrane repair. Fluorescence microscopy enables to determine the subcellular localization of candidate proteins in damaged cells while TEM offers high‐resolution ultrastructural analysis of the µm²‐disruption site, which enables to decipher the membrane repair mechanism. Here we focus on the study of human skeletal muscle cells, for obvious clinical interest, but this protocol is also suitable for other cell types. © 2018 by John Wiley & Sons, Inc.